2009
DOI: 10.1021/nl9018275
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Imaging of Molecular Assemblies in Live Cells Based on Nanoparticle Plasmon Resonance Coupling

Abstract: We used molecular-specific gold nanoparticles to monitor epidermal growth factor receptors (EGFR) in live A431 cells over time. Dark-field hyperspectral imaging, electron microscopy, and electrodynamic modeling were used to correlate optical properties of EGFR-bound plasmonic nanoparticles with receptor regulation state. We showed that receptor trafficking resulted in a progressive red-shift of greater than 100nm in the nanoparticle plasmon resonance wavelength over a time period of 60 minutes. Furthermore, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
194
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(199 citation statements)
references
References 46 publications
5
194
0
Order By: Relevance
“…An example of this is shown in Fig. 5 where DF hyperspectral imaging was used to follow the journey of Au NPs upon endocytosis: small clusters of NPs that scatter green light are present in early endosomes, before they are trafficked to late endosomes that scatter red light due to the formation of larger clusters [105].…”
Section: Spectroscopic and Microscopy Methods (Table 2)mentioning
confidence: 99%
“…An example of this is shown in Fig. 5 where DF hyperspectral imaging was used to follow the journey of Au NPs upon endocytosis: small clusters of NPs that scatter green light are present in early endosomes, before they are trafficked to late endosomes that scatter red light due to the formation of larger clusters [105].…”
Section: Spectroscopic and Microscopy Methods (Table 2)mentioning
confidence: 99%
“…Work from different groups has demonstrated that, due to the spectral shift in the spectrum of the scattered light, the near-field interactions between NP immunolabels at high ρ can be detected using conventional far-field optics. [24][25][26][27][28] The spectral shift in the ensemble-averaged NP resonance increases as the average interparticle separation between the NPs decreases with growing ρ.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Work from different groups has demonstrated that, due to the spectral shift in the spectrum of the scattered light, the near-field interactions between NP immunolabels at high ρ can be detected using conventional far-field optics. [24][25][26][27][28] The spectral shift in the ensemble-averaged NP resonance increases as the average interparticle separation between the NPs decreases with growing ρ.In this manuscript we quantify the relationship between the peak plasmon resonance wavelength (λ res ) and ρ for 40 nm diameter Au NP immunolabels targeted at EGFR on A431 cells. Immunolabeling strategies are commonly used to investigate receptor density distributions in the electron microscope, 8,29,30 where the spatial distribution of the NP labels is used to infer information about the local concentration of the targeted receptor.…”
mentioning
confidence: 99%
“…8,9,[14][15][16][17][18][19][20] The work we describe here expands and generalizes the application of nanoparticle plasmon-resonance coupling (NPRC) to monitor the dynamic behavior of large protein complexes in living cells. 21 This has important implications, as there is currently a dearth of physical methods for monitoring the behavior of large molecular complexes with high spatial and temporal resolution in living cells. We observed the trafficking mechanisms of the epidermal growth-factor receptor (EGFR), a key receptor tyrosine kinase that controls fundamental cellular processes such as DNA replication and division.…”
Section: 1117/21200912002512 Page 2/3mentioning
confidence: 99%